From Digital Religion to Digital Islam: Finding God in the Society 5.0 through Maqāsīd Sharī’ah - Abdullah Muslich Rizal Maulana; Farhah Farhah; Fadhillah Rachmawati; Annisa Syifa Mulya (Faculty of Sharia, Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
This study researches the development of Digital Islam and attempts to apply Maqāṣid al-Sharī'ah (the objectives of the Islamic law) to Society 5.0. It seeks to document the merger of traditional legal wisdom and contemporaneous digital life through content analysis. It starts by proposing an argument that Digital Religion is an important modern debate. Digital Religion is the conversion of holy signs, artifacts and religious/faith-based words from in-person to online mediums, where there is synchronous interaction between the online and offline worlds. This study maintains that Digital Islam is the most advanced expression of this phenomena. Digital interactions, directed toward the attainment of Maṣlaḥah and the avoidance of Mafsadah, ethically contain the use of technology to not be simply instrumental, but to promote good. This study, most importantly, shows how Maqāṣid al-Sharī’ah still has relevance in ‘implementing Divinity’ within an ostensibly ‘secular’ Society 5.0. Finally, it discusses the possible points of ‘friction’ and structural impediments that may occur as the intersection of Islamic Digital Ethics and the ever-accelerating, disruptive nature of the new technologies.